The effect of water quality, cultivar, and organic fertilizer on growth and yield of volatile oil carvone and limonene in Dill. Issue 4 (4th July 2022) - Al-Taey, Duraid K.A.; Burhan, Aseel K.
ABSTRACT: Scarcity of irrigation water, reduction in water quality, and increased amount of land affected by salinity are problems affecting production of dill ( Anethum graveolens L.). A field experiment was conducted to study effects of irrigation water quality (1.2 and 8 dS∙m −1 ), cultivars Esfahan and Franchi, and organic fertilizers (rice waste compost, potassium humate, and granular humate) on growth and volatile oil quantity and quality in dill. The combination of granular humate (2 kg∙ha −1 ) and rice waste compost (20 ton∙ha −1 ) had the highest dry yield (823 kg∙ha −1 ) when irrigated with 1.2 dS∙m −1 ; treatment with granular humate (2 kg∙ha −1 ) had the highest dry yield (625 kg) when irrigated with water at 8 dS∙m −1 . Treatment with rice waste compost at 20 ton∙h −1 had the highest percent of volatile oil (0.292%), yield of volatile oil (1.762 L∙ha −1 ), and percent of carvone (10.64%) when irrigated with water at 1.2 dS∙m −1 . The combination of granular humate (2 kg∙ha −1 ) and rice waste compost (20 ton∙ha −1 ) had the highest percent of volatile oil (0.184%) and yield of volatile oil (0.333 L∙ha −1 ) when irrigated with water at 8 dS∙m −1 . The cultivars differed in response to salinity of the irrigation water; fertilizer combinations reduced damage due to salinity in some dill growth parameters, and quality and quantity of dill volatile oils. Use of organic fertilizers led to improve quality and quantity of dill under saline conditions and reduce dependency on synthetic fertilizers.